Lecture, model, or both? Optimizing fracture education with 3D printing: a longitudinal interventional study - Christopher Cramer; André Strahl; Karl-Heinz Frosch; Miriam Rüsseler; Tobias Dust (3D Printing in Medicine, 2026)
Abstract Background Traditional anatomical training methods in surgery, like cadaver dissection and didactic lectures, face limitations in availability, cost, and translating 2D to 3D understanding. Three-dimensional (3D) printing offers an innovative solution for medical education, particularly in orthopedics and trauma surgery, where complex bone structures are crucial. 3D-printed models show promise for improving anatomical learning, spatial understanding, and student satisfaction. Methods This longitudinal interventional study investigated the impact of different teaching methods on medical students’ knowledge acquisition and perceptions regarding fibula fracture management. Sixty-seven 3rd or 4th-year students, randomized into three groups, participated. Group 1 received a 20-minute lecture, Group 2 engaged in model-based learning using a 3D-printed fibula model, and Group 3 received a combination of lecture and model-based learning. Knowledge was assessed via a written quiz, and subjective feedback and personal motivation were measured. Assessments occurred immediately before (t0), immediately after (t1), and four weeks after (t2) the teaching unit. Results At baseline (t0), there were no significant group differences in processing time. Immediately post-training (t1), the lecture group showed the shortest processing time. The lecture + practice group achieved the highest mean knowledge score at t1, significantly outperforming both practice and lecture groups (8.25 vs. 5.09 vs. 6.82, p < 0.01). At the four-week follow-up (t2), significant group differences persisted, with lecture + practice maintaining a significantly higher mean score than practice (5.75 vs. 3.46, p < 0.05). Overall, knowledge significantly improved from t0 to t1 and t0 to t2, though a decrease was noted between t1 and t2. Subjective feedback consistently indicated that practical and combined methods were more suitable for understanding, enhanced security, and promoted interest. Conclusions 3D models improve anatomical learning and student satisfaction. The combined lecture + model approach demonstrated superior immediate and sustained knowledge acquisition for complex topics like fracture management. This aligns with pedagogical theories such as constructivism and cognitive load theory, suggesting that integrating theoretical context with physical models optimizes learning outcomes. This study underscores the importance of rigorous comparative designs for effectively integrating innovative tools like 3D printing into medical education. Clinical trial number Not applicable.